The effect of inspiratory muscle training on high-intensity, intermittent running performance to exhaustion - Tong, T. K.; Fu, F. H.; Chung, P. K.; Eston, R.; Lu, K.; Quach, B.; Nie, J.; So, R. (Applied Physiology, Nutrition, and Metabolism, 2008)
The effects of inspiratory muscle (IM) training on maximal 20 m shuttle run performance (Ex) during Yo-Yo intermittent recovery test and on the physiological and perceptual responses to the running test were examined. Thirty men were randomly allocated to 1 of 3 groups. The experimental group underwent a 6 week pressure threshold IM training program by performing 30 inspiratory efforts twice daily, 6 d/week, against a load equivalent to 50% maximal static inspiratory pressure. The placebo group performed the same training procedure but with a minimal inspiratory load. The control group received no training. In post-intervention assessments, IM function was enhanced by >30% in the experimental group. The Ex was improved by 16.3% ± 3.9%, while the rate of increase in intensity of breathlessness (RPB/4i) was reduced by 11.0% ± 6.2%. Further, the whole-body metabolic stress reflected by the accumulations of plasma ammonia, uric acid, and blood lactate during the Yo-Yo test at the same absolute intensity was attenuated. For the control and placebo groups, no significant change in these variables was observed. In comparison with previous observations that the reduced RPB/4i resulting from IM warm-up was the major reason for improved Ex, the reduced RPB/4i resulting from the IM training program was lower despite the greater enhancement of IM function, whereas improvement in Ex was similar. Such findings suggest that although both IM training and warm-up improve the tolerance of intense intermittent exercise, the underlying mechanisms may be different.